Awakening students' entrepreneurial selves: case music in basic education. Issue 7 (8th August 2016) - Hietanen, Lenita; Ruismäki, Heikki
Abstract : Purpose: Entrepreneurship education is recommended for implementation throughout the entire educational path. However, there have been challenges in implementing entrepreneurship education for many kinds of students, especially in non-business education. The case study presented in the current paper asks how 15-year-old students in Finnish basic education are able to find their 'entrepreneurial selves' by looking at their musical activities through an 'entrepreneurial lens'. Design/methodology/approach: This case study examines an intervention carried out among music students in basic education. The music teacher interpreted the enterprise approach as guiding the students to experiment with different styles in singing and playing instruments, to seek various opportunities to sing and play both individually and as a group, and to reflect upon their activities. To awaken their entrepreneurial selves, the students were guided to assess their musical activity using 12 enterprise concepts. Findings: The study shows that students in basic education can be encouraged to reflect on their music studies by comparing their musical activities with small-sized entrepreneurs' attributes and activities. For example, the students pointed out the ability to take initiative and cooperate. One principle in organising the music learning environment was to allow the students to make choices based on their own interests. The alternatives given led students to discover opportunities and to make decisions to experiment. Their reflective practices enabled them to make new decisions and finally own and lead their music learning paths. Practical implications: This investigation shows that encouraging students to reflect on their study practices through an entrepreneurial lens may awaken them to their entrepreneurial selves regardless of the subject and context. Despite examining only music studies in basic education, the findings may prompt teachers and educators in other non-business educational contexts and subjects to apply the ideas shared in the current paper. Originality/value: Music as a subject and basic education as an educational level have not been examined in depth as enterprise learning environments. Only a few previous studies have focused mainly on non-business students' enterprise activities without training in business skills.